Combustion and physical properties of blends of military jet fuel JP-5 with fifteen different methyl ester biodiesels synthesized from edible and nonedible oils. (1st March 2022) - Luning Prak, Dianne; Hamilton, Michael; Banados, Rhea; Cowart, Jim
Graphical abstract: Highlights: Fifteen methyl ester biodiesels synthesized from edible & nonedible oils. Major biodiesel components (C13, C14, C16, C18) consistent with previous studies. Biodiesel densities > JP-5 max. density specification, some viscosities > JP-5 spec. Biodiesel flashpoints > 373 K, cetane numbers > 40, surface tension > 28.6 mN/m. Yanmar diesel engine metrics for JP-5, biodiesel, and their mixtures reported. Abstract: This study investigates the physical properties and combustion behavior of blends of military jet fuel JP-5 with biodiesels synthesized from methanol, potassium hydroxide, and 13 plant oils (avocado, canola, castor, coconut, corn grapeseed, linseed, neem, olive, palm, peanut, soybean, and walnuts), bacon grease, and duck fat. The biodiesels were analyzed using gas chromatography(GC)/mass spectrometry(MS) and GC/flame ionization detection(FID). The main components found were methyl esters with 13 to 18 carbon atoms, agreeing with previously reported compositions. Biodiesel densities ranged from 875.3 to 929.3 kg·m −3 at 15 °C, many exceeding the maximum allowable U. S. Naval diesel fuel density of 876 kg·m −3 . Biodiesel viscosities ranged from 3.05 to 15.8 at mm 2 ·s −1 at 40 °C, half of which were higher than the maximum allowable military diesel viscosity of 4.3 mm 2 ·s −1 . All biodiesel flash points were higher than the military diesel minimum requirement of 60 °C, and all the biodiesel derived cetane numbers where greater than the minimum of 42, except for castor oil, which had a DCN of 41.2. Surface tensions ranged from 28.6 to 32.4 mN·m −1, which were higher than the 26.0 mN·m −1 measured for JP-5. The bulk moduli ranged from 1678 to 2039 MPa, which were higher than the 1444 MPa for JP-5. Combustion experiments in a Yanmar diesel engine were conducted with JP-5, castor, soy, corn, coconut and palm oil biodiesels and 20% and 50% mixtures of the biodiesels in JP-5. The ignition delay (IGD) of the neat fuels decreased (shortened) as the DCN of the fuel increased. The maximum rate of heat release was highest for the castor oil and lowest for palm oil. The peak pressure location was similar for the biodiesels, except for castor oil biodiesel, which had later combustion phasing. There was only a modest increase in the thermal efficiencies of the biodiesels as compared to JP-5. Most mixtures of JP-5 and biodiesel had IGDs, maximum rates of heat release, and peak pressures that fell between the value for pure biodiesel and that of JP-5. Overall, the mixture of 20% biodiesel with JP-5 will have minimal impact on the combustion characteristics in a diesel engine.